Current Topics in Cellular Regulation Volume 31 - Horecker, Bernard L. (Current Topics in Cellular Regulation, 2014)
Current Topics in Cellular Regulation: Volume 31 is a collection of papers that deals with the role of calcium as intracellular messenger, calcium release or entry across the plasma membrane, calcium in neurotransmitter release, and the regulation of free calmodulin levels in neurons by neuromodulin. Other papers discuss the calcium/calmodulin-dependent protein kinase II, the regulation of muscular calcium channels, and the Na+-Ca2+ exchangers. One paper describes the mechanisms of intracellular calcium release or entry in which agonists acting through the phosphoinositide system, or possibly by metabolites or secondary messenger system,can regulate the mechanisms of cellular Ca2+. Another paper describes different approaches in evaluating the possible mechanisms of calcium in neurotransmitter release. The paper notes that imaging techniques can be used in the timing and order of events in the release process. Possible identification by the investigator of specific "releasing" regions at the membranes, such as active zones, can also define more precisely the exact localization of the process. One paper discusses the interaction between released calmodulin and cytoskeleton proteins that can affect polymerization and cross-linking of cytoskeleton polymers, that leads to filopodia formation or extension. The collection will prove beneficial to molecular biologists, general biologists, microbiologists, biochemists, and researchers involved in cellular biology